Before or After Transplantation? A Review of the Cost Effectiveness of Treating Waitlisted Patients With Hepatitis C. Issue 5 (May 2017) - Tapper, Elliot B.; Afdhal, Nezam H.; Curry, Michael P.
Abstract : Abstract: All patients with chronic hepatitis C virus (HCV) infections can and should be treated. 1-9 Though highly effective direct-acting antiviral therapies are costly, the price of a cure is a 1-time investment that is outweighed by future benefits. For clinicians caring for patients requiring liver transplant, the key question relates to the timing of treatment: before or after liver transplantation? On 1 hand, treating HCV often improves our patients' model for end-stage liver disease (MELD) score, decreasing costs, and potentially improving longevity by reducing our patients' risk of death and transplantation. On the other hand, there is a concern that the cured patient with decompensated cirrhosis will find themselves in "MELD purgatory" with nonprogressive liver disease but a poor quality of life. At the same time, some patients, such as those with hepatocellular carcinoma, will require liver transplant irrespective of their MELD meaning that pretransplant therapy cannot reduce costs in such settings. These important tradeoffs are often difficult reconcile for clinicians who care for patients awaiting liver transplant. Fortunately, guidance for navigating these competing concerns can be obtained from cost-effectiveness analyses. Herein, we review the available data on this approach to HCV therapy before or after liver transplant. Abstract : The authors highlight the key questions related to the timing of Hepatitis C Virus (HCV) suggesting that pretransplant eradication of HCV is more cost-effective than waiting until after transplant, except in cases where the patient's need for transplant is not modifiable, as for patients with hepatocellular carcinoma or with severe liver dysfunction.